Nanomechanical humidity detection through porous alumina cantilevers - Boytsova, Olga; Klimenko, Alexey; Lebedev, Vasiliy; Lukashin, Alexey; Eliseev, Andrey (Beilstein Journal of Nanotechnology, 2015)
We present here the behavior of the resonance frequency of porous anodic alumina cantilever arrays during water vapor adsorption and emphasize their possible use in the micromechanical sensing of humidity levels at least in the range of 10–22%. The sensitivity of porous anodic aluminium oxide cantilevers (Δf/Δm) and the humidity sensitivity equal about 56 Hz/pg and about 100 Hz/%, respectively. The approach presented here for the design of anodic alumina cantilever arrays by the combination of anodic oxidation and photolithography enables easy control over porosity, surface area, geometric and mechanical characteristics of the cantilever arrays for micromechanical sensing.
Keywords: anodic aluminium oxide; atomic force microscopy (AFM); cantilever arrays; humidity; mechanical sensor; porous alumina

(untitled) - Pellejero, I.; Agustí, J.; Urbiztondo, M. A.; Sesé, J.; Pina, M. P.; Santamaría, J.; Abadal, G. (Sens. Actuators, B, 2012)

(untitled) - Lavrik, N. V.; Sepaniak, M. J.; Datskos, P. G. (Rev. Sci. Instrum., 2004)

(untitled) - Boisen, A.; Dohn, S.; Keller, S. S.; Schmid, S.; Tenje, M. (Rep. Prog. Phys., 2011)

(untitled) - Binning, G.; Quate, C. F.; Gerber, C. (Phys. Rev. Lett., 1986)

(untitled) - Goeders, K. M.; Colton, J. S.; Bottomley, L. A. (Chem. Rev., 2008)

(untitled) - Pina, M. P.; Mallada, R.; Arruebo, M.; Urbiztondo, M.; Navascués, N.; de la Iglesia, O.; Santamaria, J. (Microporous Mesoporous Mater., 2011)

(untitled) - Hosaka, S.; Chiyoma, T.; Ikeuchi, A.; Okano, H.; Sone, H.; Izumi, T. (Curr. Appl. Phys., 2006)

(untitled) - Kuroyanagi, T.; Terada, Y.; Takei, K.; Akita, S.; Arie, T. (Appl. Phys. Lett., 2014)

(untitled) - Yang, J.; Ono, T.; Esashi, M. (Sens. Actuators, A, 2000)

(untitled) - Chen, G. Y.; Thundat, T.; Wachter, E. A.; Warmack, R. J. (J. Appl. Phys., 1995)

Scanning Force Microscopy - Sarid, D. (Oxford University Press, 1991)

(untitled) - Petukhov, D. I.; Napolskii, K. S.; Eliseev, A. A. (Nanotechnology, 2012)

Electrodeposition - Brevnov, A. D.; Mardilovich, P. (Electrochemical Micromachining and Microstructuring of Aluminum and Anodic Alumina, 2010)